Natural Disasters, Technology Diversity, and Operating Performance - Hsu, Po-Hsuan; Lee, Hsiao-Hui; Peng, Shu-Cing; Yi, Long (The Review of Economics and Statistics, 2018)
In this paper, we empirically measure the impact of natural disasters on firm-level operating performance and examine if such impact can be mitigated by technology diversification. Using major natural disasters specified by Barrot and Sauvagnat (2015) and factory location data from the toxic release inventory (TRI) database, we first find that firms with factories located in states affected by natural disasters are much less profitable. Second, we find that firms with diversified technologies are significantly less subject to the impact of natural disasters, suggesting that technology diversity enhances firms’ sustainability.